Modelagem de um sistema de apoio à nutrição clínica - Ricarte, João Vitor Gouveia (Universidade Federal Rural do Semi-Árido, 2017)
In the clinical nutrition area, the use of systems allows nutrientes to optimize calculations of diets for many different patient cases, enabling a greater precision to elaborate diets. This study aims to develop a model of a system that helps developing diets using the Unified Modeling Language (UML). A requirements elicitation process was conducted along with a health professional allowing us to develop functionalities. A query was performed with a professional in the field, which allowed to develop functionalities. Also, an analysis of existing computational tools destined to create of diets was performed, in order to make a comparison among them. Finally, a prototype of the system was developed, which led to an analysis of the functionalities collected during the study of the requirements.
Modeling a support system for clinical nutrition
Keywords: Modelagem; Engenharia de requisitos; Sistema de apoio nutricional; Modeling; Requirements engineering; Nutritional support system; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA